Immune mechanism of gut microbiota and its metabolites in the occurrence and development of cardiovascular diseases - Lu, Jing; Jin, Xiao; Yang, Shengjie; Li, Yujuan; Wang, Xinyue; Wu, Min (Frontiers in Microbiology, 2022)
The risk of cardiovascular disease (CVD) is associated with unusual changes in the human gut microbiota (GM), the most common of which are coronary atherosclerotic heart disease, hypertension, and heart failure. Immune mechanisms maintain a dynamic balance between the gut microbiota and the host’s immune system. When one side changes and the balance is broken, different degrees of damage are inflicted on the host, and a diseased state gradually develops over time. This paper summarizes the immune mechanism of GM and its metabolites in the occurrence of common CVDs, discusses the relationship between gut-heart axis dysfunction and the progression of CVD, and lists the currently proven effective methods of regulating the GM for the treatment of CVDs.